Pengaruh Kepuasan Terhadap Loyalitas Konsumen Dengan Switching Cost Sebagai Variabel Moderasi - Heru Ismadi, Florentinus (Jurnal Keuangan dan Bisnis, 2022)
Consumers will give loyalty because they are satisfied with the service they receive or consumers will switch services because they hope to find better service than what they have received. To switch to another service, a consumer must incur a switching cost. To explore this, a study was conducted at the Panti Rapih Hospital in Yogyakarta. The analytical method used is descriptive verification, so that the research analysis will produce a description of the research variables, the profile of the respondents, and the proof of the hypothesis. The effect of the moderating variable was processed by Moderation Regression Analysis (MRA). This study found that when the switching cost variable is controlled, there is a very strong influence of satisfaction on patient loyalty. When switching costs are included as an intervening variable, there is a change in the strength of the influence of satisfaction on patient loyalty. The lower the level of switching costs experienced by the patient, the weaker the influence of satisfaction on patient loyalty. Therefore, in order to maintain customer loyalty, this element of switching costs should be paid more attention to.